Modernization of Islamic Education Curriculum Reform, Reformers (Muhammad Abduh and Ahmad Dahlan) - Hasibuan, Irwan; Harahap, Hotmatua; Nasution, Fauziah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The modernization of Islamic education is a response to the challenges of the times that demand reforms in the system, curriculum, and teaching methods. This article discusses the process of reforming Islamic education through a modern approach initiated by two important figures, namely Muhammad Abduh in Egypt and Ahmad Dahlan in Indonesia. Both emphasized the importance of integration between religious science and general science, rationality in understanding Islamic teachings, and the formation of moral and progressive students' character. Their curriculum reforms rejected the stagnant traditional education system, and replaced it with a system that was more open to science, technology, and critical thinking. Through a literature review and a historical-comparative approach, this article shows that the modernization of Islamic education is not a form of secularization, but an effort to refresh Islamic values to be relevant to the contemporary social and intellectual context. Abduh and Dahlan's thoughts became the foundation for the modern Islamic education model that balances faith, knowledge, and charity, and is able to answer the challenges of globalization and the progress of modern civilization